Características agronômicas, adaptabilidade e estabilidade produtiva de genótipos de soja - Egewarth, Vanessa Aline (2019)
Soybean breeding programs in Brazil have contributed significantly to the development of more productive cultivars. However, the great extension of the country and the high sensitivity to the photoperiod of the crop becomes the selection process and the recommendation of cultivars difficult and it is necessary to carry out experimental tests in different environments to verify the effect of them on the agronomic performance and to identify superior genotypes that are more adapted and stable to the crop sides. In this sense, the present work was developed with the purpose of characterizing the development and analyzing the adaptability and phenotypic stability of 60 soybean strains, aiming at the recommendation of cultivars for the western region of Paraná. For this, experimental trials with 30 genotypes were carried out in Itaipulândia, Palotina and Campo Mourão - PR, in 2016/17 crop season and another 30 genotypes in Pato Bragado, Itaipulândia and Mamborê - PR, in the 2017/18 crop. The experimental design consisted of randomized blocks, composed of 30 genotypes, in three replications. The variables evaluated in the 2016/17 crop season were: number of days for maturation, plants height, plant population and grain yield, from that the stability and adaptability analysis by Wricke, Centroid, and Lin and Binns. In the 2017/18 crop season, the number of days for maturation, plant height at maturity, plant population, number of grains per plant, number of pods per plant and crop season were evaluated, as well as stability and adaptability analysis by methodologies of Eberhart and Russel, and Modified Centroid. It was observed that the environmental variation generated changes in the cycles of the genotypes Exp_05, Exp_06, Exp_08, Exp_09, Exp_10, NS 6535 IPRO, and TMG 7063 IPRO cultivated in the 2016/17 agricultural year in Itaipulândia, Palotina and Campo Mourão Countries. However, these genotypes stood out because they presented high grain yields, wide adaptation and productive stability. Environmental conditions unfavorable to soybean crop generated high losses for all genotypes grown in Pato Bragado, Itaipulândia and Mamborê in the 2017/18 crop season, in that the highest grain yield was achieved by genotype EXP_17 (2.324,37 kg ha-1), being considered stable and of general high adaptability.